EDUKASI DAN DEMONSTRASI PENATALAKSANAAN LUKA DI DESA BAYUNG GEDE, KINTAMANI - Permatananda, Pande Ayu Naya Kasih; Pandit, I Gde Suranaya; Riandra, Ni Putu Indah Kusumadewi; Cahyawati, Putu Nita; Lestarini, Asri (Universitas Mataram, 2024)
Bayung Gede Village is a tourist village that located in the Kintamani area and included in the cycling tourism route in Bali. Apart from that, Bayung Gede village is belong to one of vulnerable areas to rabies in Bali. This community service activity was carried out to enhance the understanding and skills of Bayung Gede Village residents in managing wounds, including the bite wounds of rabies infectious animals. The activities were started with socialization, initial discussions with partners, and the preparation of infrastructure. The provision of material was conducted through socialization, counseling methods, and wound demonstration. The monitoring and evaluation of activities is seen from three indicators, including input, process, and output indicators. In terms of input, the activity was successful as planned and attended by 15 participants who were village apparatus and villagers of Bayung Gede. Seeing from the process indicators, the participants looked enthusiastic and following the entire activity from start to finish. This activity also met the output indicators, with the majority of participants (>90%) answered the entire posttest question correctly. Through this community service, all participants are expected to independently apply all the knowledge and skills acquired from all the process and able to disseminate to other residents.